2015
DOI: 10.1007/7651_2015_300
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Circulating Melanoma Cells

Abstract: Circulating melanoma cells (CMCs) represent critical mediators of metastatic melanoma progression. However, isolation and characterization of CMCs has been challenging due to the low frequency of these cells and the paucity of melanoma-specific cell surface markers. Herein, we describe a method for the isolation of CMCs that employs two independent markers, displays high sensitivity for CMC enrichment, and can be readily adapted to include additional molecular melanoma markers of interest. CMCs isolated by thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
(32 reference statements)
0
4
0
1
Order By: Relevance
“…CMCs express a variety of surface antigens used in various isolation and detection techniques, including melanoma cell markers, e.g., MCAM (melanoma cell adhesion molecule, MCAM/MUC18/CD146) [ 25 ], MART-1 (melanoma antigen recognized by T cells 1/Melan-A) [ 29 ], MAGE-A3 (melanoma antigen A3), PAX3 (paired box 3), HMW-MAA (human high-molecular weight melanoma-associated antigen) [ 30 ] and GM2/GD2 (gangliosides) [ 31 ]. Importantly, none of the mentioned antigens’ expression is restricted to melanoma cells.…”
Section: Liquid Biopsy In Melanomamentioning
confidence: 99%
“…CMCs express a variety of surface antigens used in various isolation and detection techniques, including melanoma cell markers, e.g., MCAM (melanoma cell adhesion molecule, MCAM/MUC18/CD146) [ 25 ], MART-1 (melanoma antigen recognized by T cells 1/Melan-A) [ 29 ], MAGE-A3 (melanoma antigen A3), PAX3 (paired box 3), HMW-MAA (human high-molecular weight melanoma-associated antigen) [ 30 ] and GM2/GD2 (gangliosides) [ 31 ]. Importantly, none of the mentioned antigens’ expression is restricted to melanoma cells.…”
Section: Liquid Biopsy In Melanomamentioning
confidence: 99%
“…Analysis of some clinical data demonstrated that overexpression of ABCB5 can promote tumor progression, and that ABCB5 expression is usually low in pigmented nevus subpopulation but high in primary and metastatic melanoma cell subpopulation (37,44). In serial human-to-mouse xenotransplantation experiments, ABCB5 + melanoma cells possess greater tumorigenic capacity than ABCB5bulk populations (44,45). Ma and Frank (45) reported that ABCB5 + melanoma cells exist in the peripheral blood of patients with melanoma.…”
Section: Melanoma Metastasis Is Modulated By Molecular Markers Of Mscsmentioning
confidence: 99%
“…In serial human-to-mouse xenotransplantation experiments, ABCB5 + melanoma cells possess greater tumorigenic capacity than ABCB5bulk populations (44,45). Ma and Frank (45) reported that ABCB5 + melanoma cells exist in the peripheral blood of patients with melanoma. Subsequently, transplanting these cells to Nod/SCID/IL2 mice can induce distant metastasis, and the degree of metastasis is directly proportional to the number of ABCB5 + melanoma cells transplanted.…”
Section: Melanoma Metastasis Is Modulated By Molecular Markers Of Mscsmentioning
confidence: 99%
“…Это позволяет предположить, что АВС-транспортеры, возможно, участвуют в регуляции «стволового фенотипа» клеток, поддерживая их популяцию [46]. В целом ряде клинических исследований по изучению роли транспортного белка ABCB5 ученые установили, что гиперэкспрессия ОСК меланомы транспортера ABCB5 строго коррелирует с опухолевой прогрессией, развитием рецидивов и лекарственной резистентности [43,[47][48][49][50]. Кроме того, выраженная экспрессия медиатора ассоциирована с клоногенетическим потенциалом клеток меланомы in vitro [51][52][53].…”
Section: лекарственная резистентность и опухолевые стволовые клеткиunclassified